Dealing with pluralism: the managerial work of CEOs in Italian public healthcare organizations - Federico Lega; Andrea Rotolo; Marco Sartirana (BMC, 2022)
Abstract Background Healthcare organizations are extremely complex. The work of their CEOs is particularly demanding, especially in the public sector, though little is known about how the managerial work of a healthcare organization CEO unfolds. Drawing from scholarship on managerial work and management in pluralistic organizations, we sought to answer the questions: What is the content of managerial work of CEOs in public healthcare in Italy? How do healthcare CEOs perform their managerial work in complex interactions with multiple stakeholders? Methods For this study we adopted a multi-method approach in which we conducted a survey to investigate CEO behaviors, tracked CEO working time for 4 weeks, and conducted semi-structured interviews with senior CEOs. Results CEOs in public healthcare devote most of their time to interaction, which half of which is perceived as being occupied with apparently mundane problems. Nonetheless, devoting time to such activities is functional to a CEO's goals because change in pluralistic contexts can be achieved only if the CEO can handle the organization's complexity. CEOs do this by engaging in routines and conversations with professionals, creating consensus, and establishing networks with external stakeholders. Conclusions CEOs are called to reduce fragmentation and foster cooperation across disciplines and professional groups, with the overarching aim to achieve integrated care. Using an analytical approach we were able to take into account the context and the relational dimension of the managerial work of healthcare CEOs and the specificities of this role. Trial registration This article does not report the results of a healthcare intervention on human participants, and the material used in the research did not require ethical approval according to Italian law.